AI-Assisted Academic Writing: Perspectives of EFL Students from Three Indonesian Universities - Dewi Sartika; Eva Saptarina; Kiki Rizki Amelia; Rachmanita; Fitri Novia; Ratna Nery; Rekha Asmara (STIT Buntet Pesantren Cirebon, 2026)
The integration of Artificial Intelligence (AI) into higher education has significantly transformed academic writing instruction, especially within English as an EFL learning environment. This study employed an Explanatory sequential mixed-methods design to investigate EFL students’ perceptions of AI-assisted academic writing and identify the perceived benefits and challenges of its implementation. The participants consisted of 28 EFL students from three Indonesian universities having experience using AI tools in academic writing courses. Quantitative data were collected via closed-ended questionnaires and analyzed using descriptive statistics, while qualitative data were obtained through semi-structured in-depth interviews to explain the quantitative findings. The quantitative results revealed that students demonstrated highly positive perceptions toward the use of AI in academic writing classes, with an overall mean score of 4.32, categorized as excellent. Students perceived AI as a supportive technology for generating ideas, organizing written text, improving grammatical accuracy, and completing writing tasks more efficiently. The qualitative findings revealed four dominant themes: AI as a writing assistant, improvement of writing efficiency and quality, AI as a means of independent learning, and ethical awareness and academic responsibility. Participants reported that AI supported independent learning, provided immediate feedback, and increased confidence and creativity in writing activities. Nevertheless, students also raised concerns about becoming too dependent on AI and the potential ethical problems related to academic honesty and maintaining originality in their work. The results claim that AI has strong potential to enhance EFL academic writing instruction when integrated pedagogically and used responsibly. It also provides practical implications for EFL lecturers in designing ethical and effective AI-assisted writing instruction in higher education contexts.